Cultural Diversity and Language Education: Lessons from the European Migrant Crisis - Mukti, Muhammad Abdee Praja; Maulana, Muhamad Trian; Kamaluddin, Mohamad Ihsan; Wardoyo, Cipto (Program Studi Pendidikan Bahasa Inggris, 2024)
This study investigates the European migration crisis, focusing on its root causes, cultural conflicts, and social integration challenges. The research highlights how armed conflict, political instability, economic disparities, and climate change drive mass migration and create significant social and economic pressures on host countries. Using a systematic literature review, this paper identifies the main barriers to integration, including language differences, discrimination, and unequal access to resources. The findings emphasize the importance of comprehensive policies that promote social cohesion, inclusive integration programs, and international cooperation to address migration flows and humanitarian concerns effectively. This research contributes to the ongoing discussion on sustainable migration policies by providing insights into both immediate and long-term strategies for managing migration challenges.